Comparing the traditional and Multiple Mini Interviews in the selection of post-graduate medical trainees - Sklar, Michael; Eskander, Antoine; Dore, Kelly; Witterick, Ian (Canadian Medical Education Journal, 2015)
Background: The traditional, panel style interview and the multiple mini interview (MMI) are two options to use in the selection of medical trainees with each interview format having inherent advantages and disadvantages. Our aim was to compare the traditional and MMI on the same cohort of postgraduate applicants to the Department of Otolaryngology – Head & Neck Surgery at the University of Toronto. Method: Twenty-seven applicants from the 2010 Canadian Residency Matching Service selected for interview at the University of Toronto, Department of Otolaryngology – Head & Neck Surgery were included in the study. Each applicant participated in both a traditional interview and MMI. Results: Traditional interviews marked out of a total maximum score of 570. On the traditional interview, scores ranged from 397-543.5 (69.6 - 95.3%), the mean was 460.2. The MMI maximum score was out of 180. MMI scores ranged from 93 – 146 (51.7 - 81.1%) with a mean of 114.8. Traditional interview total scores were plotted against MMI total scores. Scores correlated reasonably well, Pearson Correlation = 0.315 and is statistically significant at p = 0.001. Inter-interview reliability for the two interview methods was 0.038, with poor overall agreement 0.07%. Conclusions: MMI and traditional interview scores are correlated but do not reliably lead to the same rank order. We have demonstrated that these two interview formats measure different characteristics. One format may also be less reliable leading to greater variation in final rank. Further validation research is certainly required. Key Words: Multiple mini interview; medical education; traditional interview; postgraduate admissions